2012
DOI: 10.1080/11250003.2012.663003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of claw geometrical characteristics among birds of prey and non-raptorial birds

Abstract: It has long been held that Falconiformes and Strigiformes possess a strong similarity in their claws due to their adaptive convergence for preying specialisation and that claws differ from those of other bird species, justifying the usual name of talons, instead of claws. It is subjectively felt that talons in birds of prey are very similar and somewhat different from claws of other birds, but the analysis of the geometrical reason for that has been neglected so far. The aim of this study is to answer two ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 22 publications
4
31
1
2
Order By: Relevance
“…The correlation is poorer than that reported in previous studies [4], [66], with behavioural categories showing opposite trends to the results found here. The claw mid-point height, however, correlates well with mass, similar to the result reported by Pike and Maitland [4].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The correlation is poorer than that reported in previous studies [4], [66], with behavioural categories showing opposite trends to the results found here. The claw mid-point height, however, correlates well with mass, similar to the result reported by Pike and Maitland [4].…”
Section: Discussioncontrasting
confidence: 99%
“…Manning et al [32] concluded that “the feet and hands of dromaeosaurs functioned both for locomotion (walking, running, and climbing) and as prey capture/grappling devices”, though our data for digit III supports only a terrestrial interpretation. Deinonychus , however, does fall within the predatory category, suggesting that its foot may have been used in prey immobilisation behaviour analogous to modern Accipitridae [66], [69].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there was a previously unrecognized confounding factor present in the data, high intraspecific variation. Some previous studies used up to six specimens per species when examining claw shape (Birn‐Jeffery et al, ) while some other studies have used a single individual per species (Csermely et al, ). When we examined several species that had high sample sizes in our dataset ( n > 18) very high intraspecific variation was observed, whether using traditional measurements or geometric morphometric analyses (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Taxa were then split into three ecological groups (predominantly predatory, predominantly ground‐dwelling, and flying generalists) to assess how claw shape related to ecology. Birds of prey (e.g., Accipitriformes, Strigiformes, Falconiformes) were classified as predominantly predatory birds given the unique ways that they use their claws in prey capture (Brown & Amadon, ; Csermely et al, ; Csermely & Rossi, ; Del Hoyo, Hoyo, Elliott, & Sargatal, ; Johnsgard, ). Birds were considered predominantly ground‐dwelling birds if they spend the majority of their time, or all of their time, on the ground (e.g., ratites, bustards, some Galliformes; Del Hoyo et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation